Early hydroxychloroquine and azithromycin as combined therapy for COVID-19: a case series - Siswanto Siswanto; Oktaviarum S. Utama; Agit S. Adisetiadi; Maria E. Pranasakti; Mohamad Saifudin Hakim (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Coronavirus disease 2019 (COVID-19) is a worldwide outbreak caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The World Health Organization (WHO) has declared it as a public health emergency of international concern (PHEIC) and eventually a pandemic. Many clinical trials have been conducted to investigate potential and effective therapies for COVID-19. Here we reported the outcome of three COVID-19 cases treated early with the combination of hydroxychloroquine and azithromycin. Early treatments of suspected or confirmed positive COVID-19 cases with this combination therapy is to avoid disease progressions into a more severe and irreversible state. In these cases, clinical, radiological, and laboratory features were followed up. No complications were observed. The COVID-19 patients treated with this early combination therapy showed good clinical and virological responses.